Menggagas Pengawasan Badan Perwakilan dalam Kabinet Presidensial: Perspektif Perbandingan Hukum - Buana, Mirza Satria (Undang: Jurnal Hukum, 2023)
This article analyses the controlling function of external institution toward government cabinet, under the light of checks and balances principles. This article believes that a professional controlling mechanism conducted by the DPR and DPD would create a more responsible government cabinet. The effectiveness of cabinet is determined by both internal and external control mechanism. This article uses ius constituendum approach to consider the possibility to selectively transplant the Westminster’s government accountability mechanism. The discourse is whether or not it can be adopted within Presidential system. This article also considers an ideal design for the DPR and DPD to control government cabinet. In order to analyses these issues, this article uses legal method in accompanying with comparative approach. This article concludes that, theoretically, presidential system of government also aims to a responsible government. Therefore, control to government cabinet is democratically acceptable. In the perspective of ius constituendum, this essay offers a selective-legal transplant in constructing a shadow cabinet aiming to critically control and question government cabinet (ministers), especially regarding their policies and internal regulations. Specifically on internal regulations, shadow cabinet could potentially initiate a progressive mechanism, namely Post-Legislative Scrutiny (PLS) to review ministerial regulations. Abstrak Artikel ini menganalisa fungsi pengawasan kinerja kabinet oleh organ eksternal dalam bingkai checks and balances. Dengan hadir dan efektifnya relasi pengawasan yang profesional-konstruktif oleh DPR dan DPD, kerja kabinet menjadi lebih akuntabel dan efektif. Efektivitas kabinet presidensial ditentukan oleh baik atau tidaknya sistem pengawasan internal maupun eksternal dalam sistem pemerintahan. Artikel ini mengedepankan pendekatan ius constituendum dengan mencermati praktik baik (good practice) sistem akuntabilitas pemerintahan Westminster. Diskursus yang diketengahkan adalah: apakah sistem akuntabilitas Westminster dapat ditransplatasi secara selektif dengan sistem Presidensial di Indonesia? Kemudian artikel ini menimbang desain relasi pengawasan DPR dan DPD terhadap kabinet pemerintahan. Guna menganalisa secara komprehensif, artikel ini menggunakan metode hukum normatif dengan pendekatan perbandingan hukum. Artikel ini berkesimpulan bahwa secara teoretis, sistem pemerintahan presidensial berorientasi pada tujuan pemerintahan yang bertanggung-jawab (responsible government), sehingga pengawasan menteri-menteri kabinet oleh lembaga legislatif adalah sebuah mekanisme yang demokratis. Dalam perspektif ius constituendum, artikel ini menawarkan transplantasi-selektif terhadap mekanisme kabinet bayangan atau shadow cabinet, dengan fokus pengawasan terhadap tindakan dan kebijakan eksekutorial menteri-menteri. Lebih spesifik terkait produk perundang-undangan kementerian, ‘kabinet bayangan’ dapat berperan konstruktif dengan melakukan post-legislative scrutiny (PLS) terhadap produk-produk perundang-undangan.